2016
DOI: 10.1007/s13201-016-0386-3
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption studies of Cu(II) on Boston fern (Nephrolepis exaltata Schott cv. Bostoniensis) leaves

Abstract: Adsorption studies were done on Boston fern leaves for the effective removal of Cu(II) ions from aqueous solution. It has been tested for the first time for heavy metal adsorption from aqueous solution. This promising material has shown remarkable adsorption capacity towards Cu(II) ions which confirm its novelty, ease of availability, non-toxic nature, cheapness, etc., and give the main innovation to the present study. The adsorbent was analyzed by FT-IR, SEM and EDS. The effect of pH, contact time, initial me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…4). Maximum adsorption capacity of ATCUS towards Cu(II) investigated in the present study was found to be greater than various other adsorbents reported earlier (Table 3) (Rao and Ikram, 2011;Arshadi et al, 2014;Rao and Khan, 2016;Rao and Khan, 2009;Rao and Kashifuddin, 2012). The contact time required to reach equilibrium was found to be dependent on initial Cu(II) concentration.…”
Section: Effect Of Initial Cu(ii) Concentration and Contact Timecontrasting
confidence: 56%
“…4). Maximum adsorption capacity of ATCUS towards Cu(II) investigated in the present study was found to be greater than various other adsorbents reported earlier (Table 3) (Rao and Ikram, 2011;Arshadi et al, 2014;Rao and Khan, 2016;Rao and Khan, 2009;Rao and Kashifuddin, 2012). The contact time required to reach equilibrium was found to be dependent on initial Cu(II) concentration.…”
Section: Effect Of Initial Cu(ii) Concentration and Contact Timecontrasting
confidence: 56%
“…The obtained results showed that the adsorption followed the physical adsorption mechanism. Negative values of ΔQ ads showed that the reaction was exothermic (Rao and Khan 2017;Ribas et al 2020).…”
Section: Thermodynamics Studiesmentioning
confidence: 99%
“…The ΔS values were also negative for Ni 2+ (-192.12 J mol -1 ) and Pb 2+ (-21.30 J mol) suggesting that there was lowering of randomness at the solidliquid interface which could be a consequence of fixation of the metal ions on the surface of the adsorbent. Conversely, a positive value obtained for Cd 2+ indicates increase in randomness at the interface and good affinity between the metal ion and the adsorbent surface Dawodu, 2016, Rao andKhan, 2017).…”
Section: E Thermodynamics Of Adsorption Of Heavy Metals On Raw Kaolin...mentioning
confidence: 99%